Property value assessment growth limits, tax base erosion and regional in-migration - Mark Skidmore; Mehmet Serkan Tosun (Institute for the Study of Labor (IZA), 2010)
In 1994 a limit on the growth of property values for tax purposes was imposed in Michigan. One consequence of the newly imposed assessment growth cap was an emerging differential in tax prices between potential new property owners and long-time property owners. The purpose of this paper is to examine the impact of this growing tax price differential on migration patterns. Using county level data on migration activity over the 1994-2006 period, we present evidence that differential tax prices resulting from the assessment growth cap have reduced in-migration.
Keywords: H71; H73; J61; 330; Property tax; tax base erosion; regional migration; Michigan; Grundsteuer; Steuerreform; Steuerbemessung; Steuerwirkung; Binnenwanderung; Michigan